Extraction and characterization of collagen and gelatin from body wall of sea cucumbers stichopus horrens and holothuria arenicola - Noora Barzkar; Gilan Attaran-Fariman; Ali Taheri; Balu Alagar Venmathi Maran (PeerJ, Inc., 2024)
Background: Marine invertebrates, including sponges, molluscs, jellyfish, mussels, and sea cucumbers, are abundant sources of high-quality collagen and offer advantages such as availability, ease of processing, lower inflammatory response, and good metabolic compatibility. Approximately 70% of the total protein in the body wall of sea cucumbers is collagen. Gelatin is a water-soluble protein produced from heat-denatured collagen and has various industrial applications.